Reduced Complexity of Pulse Rate Is Associated With Faster Cognitive Decline in Older Adults - Chenlu Gao; Andrew S. P. Lim; Shahab Haghayegh; Ruixue Cai; Jingyun Yang; Lei Yu; Agustin Ibanez; Aron S. Buchman; David A. Bennett; Lei Gao; Kun Hu; Peng Li (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Cardiovascular diseases are closely linked to cognitive health. Subclinical cardiovascular functional changes, such as cardiac autonomic dysfunction, precede cardiovascular diseases and improve risk stratification. Continuous monitoring of heart rate or pulse rate is a commonly used approach to evaluate cardiac cycle and autonomic regulation. We investigated whether the complexity of pulse rate is associated with longitudinal cognitive decline in older adults. Methods Overnight pulse oximetry data were collected from 503 participants (mean age=82±7 [SD] years, 76% female). We used a previously established distribution entropy algorithm to extract the complexity of pulse rate as a proxy for subclinical cardiovascular function. Participants completed a standardized cognitive test battery during the same visit of pulse oximetry and at least 1 follow‐up visit. Linear mixed‐effects models were conducted to test whether distribution entropy is associated with longitudinal changes in global cognition and separately, in 5 cognitive domains. Results Greater distribution entropy (ie, better complexity) was associated with a slower decline in global cognition; the effect of 1‐SD increase in distribution entropy was equivalent to being approximately 3 years younger. No associations were observed between conventional time‐ or frequency‐domain pulse rate variability measures and cognitive changes. Conclusions Higher complexity of pulse rate is linked with slower cognitive decline in older adults. Future studies should test whether complexity is also associated with future risks of neurodegenerative disorders, such as dementia, and further elucidate the causal directions.